Extracranial schwannoma in the carotid space: A retrospective review of 91 cases. Issue 1 (21st July 2016) - Zheng, Xiaoke; Guo, Kai; Wang, Hongshi; Li, Duanshu; Wu, Yi; Ji, Qinghai; Shen, Qiang; Sun, Tuanqi; Xiang, Jun; Zeng, Wei; Chen, Yaling; Wang, Zhuoying
Abstract: Background: Schwannomas of the vagus nerve and cervical sympathetic nerve are rare; hence, only limited information exists regarding their diagnosis and clinical management. Methods: We conducted a retrospective review of the clinical features, imaging studies, and treatment results of patients with schwannoma of the vagus nerve and schwannoma of the sympathetic nerve. Results: Of 91 patients, 91% (n = 83) were preoperatively diagnosed with schwannoma tumors. Using the hyoid bone as an anatomic landmark, the location of the schwannoma of the vagus nerve in the carotid space was significantly different to the location of schwannoma of the sympathetic nerve ( p  = .003). Although 52 of the 76 patients followed up (68%) had postoperative nerve weaknesses, 13 patients (50%) and 14 patients (53.8%), respectively, fully recovered from schwannoma of the vagus nerve and schwannoma of the sympathetic nerve. Conclusion: In the carotid space, schwannomas of the vagus nerve are usually located below the hyoid bone, whereas schwannomas of the sympathetic nerve more commonly arise from the suprahyoid compartment. Accurate preoperative diagnosis and the intracapsular enucleation surgical approach decreased the incidence of postoperative morbidity. © 2016 Wiley Periodicals, Head Neck 39: 42–47, 2017